The Role of Mitochondria in Mood Disorders: From Physiology to Pathophysiology and to Treatment - Giménez-Palomo, Anna; Dodd, Seetal; Anmella, Gerard; Carvalho, Andre F.; Scaini, Giselli; Quevedo, Joao; Pacchiarotti, Isabella; Vieta, Eduard; Berk, Michael (Frontiers in Psychiatry, 2021)
Mitochondria are cellular organelles involved in several biological processes, especially in energy production. Several studies have found a relationship between mitochondrial dysfunction and mood disorders, such as major depressive disorder and bipolar disorder. Impairments in energy production are found in these disorders together with higher levels of oxidative stress. Recently, a number of agents capable of enhancing antioxidant defenses or mitochondrial functioning have been studied for the treatment of mood disorders as adjuvant therapy to current pharmacological treatments. A better knowledge of mitochondrial physiology and pathophysiology might allow the identification of new therapeutic targets and the development and study of novel effective therapies to treat these specific mitochondrial impairments. This could be especially beneficial for treatment-resistant patients. In this article, we provide a focused narrative review of the currently available evidence supporting the involvement of mitochondrial dysfunction in mood disorders, the effects of current therapies on mitochondrial functions, and novel targeted therapies acting on mitochondrial pathways that might be useful for the treatment of mood disorders.